Effects of esketamine on postoperative pain, anxiety, depression, sleep, and inflammation in pregnancies undergoing cesarean section: A randomized controlled trial - Yijun Wang; Xiaolu Lin; Xiang Zou; Renqin Zhang; Juanxia Xing; Li Zhang; Jie Shen; Xiaoliang Zhang; Daju Zhou; Junhua Zhang (PLoS ONE, 2026)
Objective Postoperative pain is the most notable issue after cesarean section (CS). The contributing factors include hyperalgesia, anxiety, depression, sleep disorders, and inflammation. In this study, we explored the effects of esketamine on pain, hyperalgesia, depression, anxiety, sleep disorders, and inflammation after CS. Methods This randomized, blinded, controlled trial enrolled single-term pregnant women scheduled for elective CS. This trial was a single-center study conducted at Chongqing University Fuling Hospital. A simple randomization method was used. SPSS version 26.0 generated random numbers. The participants were randomly included in the esketamine group (group E: intravenous esketamine 0.5 mg/kg + sufentanil 4 μg/kg followed by patient-controlled intravenous analgesia with esketamine 0.5 mg/kg) or the control group (C: normal saline + sufentanil 4 μg/kg PCIA). The primary outcome was the maximum pain numerical rating scale (NRS) score within 24 h postoperatively. The secondary outcomes included pain NRS scores for moving incision, visceral, and rest incision pain at 0–6 h, 6–12 h and 12–24 h; pressure pain threshold and tolerance at 30 min and 24 h postoperatively; PCIA drug consumption, number of compressions, and dosage of rescue analgesics; time to first PCIA compression; serum C-reactive protein (CRP) at 24 h; incidence of drug-related side effects; and rates of anxiety, depression, and sleep disorders on postoperative day 2. Results Ninety-eight women were randomly included in group E (n = 50) or C (n = 48). Group E showed significantly lower maximum NRS pain scores within 24 h (5 [4–5] vs. 6 [5–6], P < 0.0001) and relieved rest incision, visceral, and moving incision pain at all time points. The PCIA compression was significantly delayed and CRP levels, as well as the incidence of postoperative depression, anxiety, and sleep disorders, were lower in group E. There were no statistically significant differences in hyperalgesia or side effects between the groups. Conclusion Intravenous esketamine could effectively reduce postoperative pain, psychological disorders, and inflammation after CS. This study was registered in the Chinese Clinical Trial Registry with registration number ChiCTR2300078310.